Rethinking the Effects of Capitalism on Individual’s Identity and the Moulding of Values in Teju Cole’s Every Day is for the Thief (2014) - DIAF ,Dacine; Mouissa, Fattoum (Faculty of Letters and Foreign Languages Department of English, 2024)
Exploring capitalism and its undesirable effects on people’s psyches have caught the interest of many sociologists, economists, and psychologists, like Karl Marx, Frederich Engel and Melvin Seeman, to name a few. Accordingly, many works of literature have portrayed the social effects of capitalism on society, like the novel North and South by Elizabeth Gaskell. Teju Cole, in this context, plighted his novella Every Day is for the Thief (2014) with the damaging bearings of capitalism on people. Although the novel does not overtly discuss capitalism; nonetheless, its depiction of characters and their values provides a strong connection to the underlying capitalist system. The author of this novel depicts identity through the protagonist, who is both a local and an outsider, as he goes on a journey of rediscovery in Lagos. The objective of this research is to put focus on the connection between capitalism, human values, and personal identity formation in post-colonial Nigeria. This dissertation, as a result, analyses the effects that a capitalist economy has on the values held by the characters and the effect of a consequently destabilised society on identity formation. In accordance with the themes discussed, an interdisciplinary approach was used, comprising the psychoanalytical, the humanistic, and the historical approaches. The Psycho-analytical approach is used in order to extract the effects of capitalism on the psyche of the characters. Similarly, the humanistic approach is embraced to examine how values can be affected by such a system and to understand the ever-changing nature of beings. The analysed novel has evidently expounded that capitalism does indeed affect both human values and identities, as it is revealed through the protagonist and the characters he encountered in the novella.